2017
DOI: 10.3390/app7100976
|View full text |Cite
|
Sign up to set email alerts
|

New Chaotic Dynamical System with a Conic-Shaped Equilibrium Located on the Plane Structure

Abstract: Featured Application: Theoretical foundations provided in this contribution demonstrate that the existence of chaos is not bound to mathematical models and electronic circuits with singular equilibrium points. The practical part of this work proves that a structurally stable hidden chaotic attractor can be both excited and experimentally observed in a lumped electronic circuit; that is, it can be measured by a digital oscilloscope.Abstract: This paper presents a new autonomous deterministic dynamical system wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…47 and a comprehensive study of another di®erent \hyperbolic" case can be found in Ref. 48. The¯rst one can be expressed as (2) with the auxiliary functions…”
Section: Model With Hyperbolic and Parabolic Equilibriummentioning
confidence: 99%
“…47 and a comprehensive study of another di®erent \hyperbolic" case can be found in Ref. 48. The¯rst one can be expressed as (2) with the auxiliary functions…”
Section: Model With Hyperbolic and Parabolic Equilibriummentioning
confidence: 99%
“…Recently there has been growing attention in finding chaotic systems with special qualities. Systems with no equilibrium [3], [4], with stable equilibria [5], [6], with curves of equilibria [7][8][9], with surface of equilibria [10][11][12], with multi-scroll attractors [13], with hidden attractors [14], [15], with amplitude control [16], [17], with simplest form , having hyperchaos [18][19][20], having fractional order form [21][22][23], with topological horseshoes [24], [25], and with extreme multistability [26][27][28][29], are examples of them. Another major category of chaotic systems includes periodically-forced nonlinear oscillators [30].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a hidden attractor has a basin of attraction which does not contain neighbourhoods of equilibrium points. Classical examples of self-excited attractors are Lorenz system [32] [42]), chaotic systems with infinite number of equilibrium points ( [43]- [44]), chaotic systems with stable equilibrium points ( [45]- [46]) and chaotic systems with line equilibrium ( [47]- [48]). A special case of the hidden attractors is a multi-stability and coexistence of attractors can be searched on ([49]- [52]).…”
Section: Introductionmentioning
confidence: 99%